Anterior substitutional urethroplasty using a biomimetic poly‐l‐lactide nanofiber membrane: Preclinical and clinical outcomes. Issue 3 (11th March 2022) - Song, Lujie; Deng, Kunxue; Yuan, Wei; Zhang, Jing; Lin, Jiahao; Hu, Xiaoyong; Huang, Jianwen; Zhang, Kaile; Zhang, Haitao; Si, Jiemin; Li, Hongbin; Xu, Tao; et al.
Abstract: The aim of this study is to investigate the feasibility and efficacy of a novel biomimetic poly‐l ‐lactide (PLLA) nanofiber membrane in repairing anterior urethral strictures from both preclinic and clinic. Biomimetic PLLA membrane was fabricated layer by layer according to the structure of human extracellular matrix. Microstructure, tensile strength, and suture retention strength were fully assessed. Before the clinical application, the safety and toxicology test of the biomimetic PLLA membrane was performed in vitro and in experimental animals. The patients underwent urethroplasty used dorsal onlay or lateral onlay technique. Then, they were followed up for 1 month, 3 months, 6 months, and then annually after the surgery. The mechanical experiments showed well property for application. Biomimetic PLLA membrane was safe according to the in vitro and animal studies. Then, a total of 25 patients (mean age 48.96 years) were included in the study from September 2016 to December 2018. After a mean follow‐up of 33.56 months, 20 patients successfully treated with biomimetic PLLA membrane. Five patients (2 bulbar and 3 penile) suffered postoperational urethral stricture recurrence. None of infection or urinary fistula or any other adverse events related to the use of biomimetic PLLA membrane were observed during the follow‐up period for all patients. The preliminary result confirmed the feasibility and efficacy of the biomimetic PLLA membrane as a novel material for anterior urethral repair. The long‐term effects with more patients should be investigated in further studies.